2012
DOI: 10.3109/00365513.2011.652158
|View full text |Cite
|
Sign up to set email alerts
|

Imbalance of regulatory T cells to Th17 cells in IgA nephropathy

Abstract: Imbalance of Treg/Th17 found in IgAN may play a role in disease pathogenesis and progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
57
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(65 citation statements)
references
References 29 publications
3
57
0
Order By: Relevance
“…42 Our flow cytometry studies suggest that increased IL-17 + neutrophils could be a potential source for increased IL-17 in THP 2/2 kidneys. At this time, we cannot completely rule out additional sources of increased IL-17 in THP 2/2 kidneys such as parenchymal or stromal cells, 43 and this is currently the topic ongoing investigations in the laboratory.…”
Section: Discussionmentioning
confidence: 98%
“…42 Our flow cytometry studies suggest that increased IL-17 + neutrophils could be a potential source for increased IL-17 in THP 2/2 kidneys. At this time, we cannot completely rule out additional sources of increased IL-17 in THP 2/2 kidneys such as parenchymal or stromal cells, 43 and this is currently the topic ongoing investigations in the laboratory.…”
Section: Discussionmentioning
confidence: 98%
“…It was shown that patients with MsPGN have increased peripheral Th17 cells and serum or urinary IL-17 levels [23, 24], CD4 T cells and Th1 cytokines also contribute to the development of the Thy-1 nephritis model, and the suppression of cytokine production could be a valid target for therapy [25-27]. The cell cycle protein kinase inhibitor p27 kip1 negatively regulates the cell cycle [28].…”
Section: Discussionmentioning
confidence: 99%
“…These are IL-17-producing Th17 cells that contribute to the progression of inflammation [10, 11] and Foxp3 + T regulatory cells which are natural suppressors that control overactive cells [12, 13]. A balance between Th17 and Treg subsets is crucial for immune homeostasis, however it was shown to be impaired in various clinical disorders [14–20]. The balance between Tregs and Th17 is controlled by IL-6.…”
Section: Introductionmentioning
confidence: 99%